The Earliest Use in English of the Term Capital - Hatfield, Henry Rand (Quarterly Journal of Economics, 1926)
Journal Article The Earliest Use in English of the Term Capital Get access Henry Rand Hatfield Henry Rand Hatfield University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 3, May 1926, Pages 547–548, https://doi.org/10.2307/1885177 Published: 01 May 1926